Diagnosis of bipolar disorders and body mass index predict clustering based on similarities in cortical thickness—ENIGMA study in 2436 individuals. (16th December 2021) - McWhinney, Sean R.; Abé, Christoph; Alda, Martin; Benedetti, Francesco; Bøen, Erlend; del Mar Bonnin, Caterina; Borgers, Tiana; Brosch, Katharina; Canales‐Rodríguez, Erick J.; Cannon, Dara M.; Dannlowski, Udo; Diaz‐Zuluaga, Ana M.; et al.
Abstract: Aims: Rates of obesity have reached epidemic proportions, especially among people with psychiatric disorders. While the effects of obesity on the brain are of major interest in medicine, they remain markedly under‐researched in psychiatry. Methods: We obtained body mass index (BMI) and magnetic resonance imaging‐derived regional cortical thickness, surface area from 836 bipolar disorders (BD) and 1600 control individuals from 14 sites within the ENIGMA‐BD Working Group. We identified regionally specific profiles of cortical thickness using K‐means clustering and studied clinical characteristics associated with individual cortical profiles. Results: We detected two clusters based on similarities among participants in cortical thickness. The lower thickness cluster (46.8% of the sample) showed thinner cortex, especially in the frontal and temporal lobes and was associated with diagnosis of BD, higher BMI, and older age. BD individuals in the low thickness cluster were more likely to have the diagnosis of bipolar disorder I and less likely to be treated with lithium. In contrast, clustering based on similarities in the cortical surface area was unrelated to BD or BMI and only tracked age and sex. Conclusions: We provide evidence that both BD and obesity are associated with similar alterations in cortical thickness, but not surface area. The fact that obesity increased the chance of having low cortical thickness could explain differences in cortical measures among people with BD. The thinner cortex in individuals with higher BMI, which was additive and similar to the BD‐associated alterations, may suggest that treating obesity could lower the extent of cortical thinning in BD.